History of the meteorological observatoions in Debrecen - Szegedi, Sándor (Acta Geographica Debrecina Landscape & Environment series, 2008)
Debrecen was among the first cities in Hungary where meteorological observatories were established, although the weather station of our University was put into operation 80 years ago, Meteorological observations have a much longer history in the city. In the present paper history of the meteorological observations and stations worked in the city has been reviewed with special emphasis on the meteorological observatory of the University of Debrecen.